Hepatotoxic Assessment of Tramadol-Diclofenac Use: A Study in a Rat Model - Elias Adikwu; Ebinyo Clemente Nelson (Biology, Medicine, & Natural Product Chemistry, 2019)
The concurrent use of tramadol and diclofenac may increase hepatotoxic risk due to their individual hepatotoxic effects. This study assessed the hepatotoxic effect of tramadol-diclofenac administration in albino rats. Twenty-four adult male albino rats (200-220g) randomized into four groups were orally administered with tramadol (12mg/kg/day), diclofenac (6mg/kg/day) and tramadol-diclofenac for 14 days respectively. The rats were anesthetized, blood samples were collected and evaluated for serum liver function and lipid parameters. Liver samples were weighed and evaluated for biochemical parameters and histology. The effects of tramadol-diclofenac on the body and liver weights did not differ significantly (p>0.05) when compared to control. Also, effects were not significant (p>0.05) on blood glucose, and serum cholesterol, triglyceride, low and high density lipoprotein cholesterol levels when compared to control. Liver and serum levels of aminotransferases, alkaline phosphatase, lactate dehydrogenase, gamma–glutamyl transferase, conjugated bilirubin and total bilirubin increased significantly in rats treated with tramadol (p<0.05), diclofenac (p<0.01) and tramadol-diclofenac (p<0.001) when compared to control. Furthermore, significant decreases in liver catalase, glutathione, superoxide dismutase, glutathione peroxidase levels with significant increases in malondialdehyde levels occurred in rats treated with tramadol (p<0.05), diclofenac (p<0.01) and tramadol-diclofenac (p<0.001) when compared to control. Hepatocyte necrosis was observed in rats treated with tramadol-diclofenac. Tramadol-diclofenac may increase hepatotoxic risk at doses used for this study.